160k views
4 votes
\left(a+b\right)^2 hihihihihiihihihihihih

1 Answer

2 votes

Consider, we need to find the expanded form of the given expression.

Given:

The expression is:


\left(a+b\right)^2

To find:

The expanded form of the given expression.

Solution:

We have,


\left(a+b\right)^2

It can be written as:


\left(a+b\right)^2=(a+b)(a+b)

Using distributive property of multiplication over addition, we get


\left(a+b\right)^2=a(a+b)+b(a+b)


\left(a+b\right)^2=a(a)+a(b)+b(a)+b(b)


\left(a+b\right)^2=a^2+ab+ab+b^2


\left(a+b\right)^2=a^2+2ab+b^2

Therefore, the expanded form of the given expression is
a^2+2ab+b^2.

User Gavin Gilmour
by
6.3k points